Porfirinas/metaloporfirinas derivadas do cardanol para aplicação em OLEDs e terapia fotodinâmica - Lima, Nayane Maria de Amorim (2020)
The present work involves the synthesis of macromolecules, specifically porphyrins and their derivatives metallized with Zn, Cu and Pd. All compounds were obtained from Cashew Nut Shell Liquid (CNSL) and have applications in two different scientific fields: electronic, with the manufacture of Organic Light Emitting Diodes (OLEDs) and medicinal, with the treatment of photodynamic therapy in the control of Cutaneous Leishmaniasis. In the electronic sphere, it is clear that in recent years research involving more sustainable products and processes has intensified. In this regard, the technology of optoelectronic devices based on organic semiconductors has turned its attention to the development of products with lower energy consumption, low production costs and that are sustainable. In this work, the meso-tetra[4-(2-(3-n-pentadecylphenoxy)ethoxy]phenylporphyrin (H2P) and its derivatives metallized with Zn and Cu, obtained from the CNSL, were applied as emitting layers in OLEDs. These compounds were characterized by absorption spectroscopy in the UV-Vis region and fluorescence emission in solution and in the solid state. Cyclic voltammetry analysis was performed to determine the HOMO and LUMO energy levels of these compounds in order to select the adjacent layers for the assembly of the device.The electroluminescent properties of the produced OLEDs were also analyzed.The results showed emission in red, a characteristic factor of porphyrins. The OLED using ZnP , presented a better performance in relation to the others, starting to operate at a voltage of 4 V, with maximum irradiance of 10 μW/cm2 and a current density (J) of 15 mA/cm2 at 10 V, which leads to better stability and greater radiant flow of light. CuP-based OLED, on the other hand, proved to be a favorable material for the design of infrared OLEDs. These results suggest that porphyrins derived from a renewable source such as CNSL, are a promising material to be used in organic devices such as OLEDs, contributing to a more sustainable optoelectronic system. In the medical aspect, it was worked with Neglected Tropical Diseases (NTDs), which are considered endemic diseases that affect poor populations and with difficulty in accessing basic health care. The lack of interest from the competent authorities and the low investment in research for the treatment and/or cure of these diseases, end up causing a major public health problem what presenting as consequence the social inequality. Among NTDs, Cutaneous Leishmaniasis (CL) appears in constant evolution in the number of cases in Brazil, mainly in the North and Northeast regions. The drugs used face challenges related to side effects and the development of resistance by the parasites. In this respect, Photodynamic Therapy (PDT) appears as a promising alternative to the treatment of CL, since in addition to not being invasive, it has minimal side effects. The present work involves the synthesis and characterization of the new meso-metalloporphyrin Pd (II) meso-tetra[4-(2-(3-n-pentadecylphenoxy)ethoxy]phenylporphyrin (PdP), obtained from the CNSL. The PdP complex was used as a photosensitizer (PS) in PDT for the treatment of CL. An analysis of singlet oxygen generation, one of the fundamental parameters of PDT, was performed, showing a singlet oxygen quantum yields of 0.49, which favors a type II photochemical reaction.The result of the photodynamic experiment carried out on the promastigotes forms of Leishmania braziliensis indicated that all tests containing PdP showed mortality of the parasite when exposed to light. Metalloporphyrin at a concentration of 100 μg.mL-1 showed the best result, as it damaged 70% of the cells when compared to the control. The treatment did not show considerable toxicity in macrophages, indicating the cell viability of the compound. Finally, it was demonstrated that obtaining meso-metalloporphyrin from biomass represents an interesting therapeutic drug in the treatment of CL, through PDT, especially for patients with intolerance to the chemotherapeutic drugs currently provided.